Probabilistic safety assessment of portable equipment applied in VVER-1000/V446 nuclear reactor during loss of ultimate heat sink accident for stress test program development - Tabadar, Z.; Ansarifar, G.R.; Pirouzmand, A. (Progress in nuclear energy (New series), 2019)
After the Fukushima Daiichi nuclear accident, all EU nuclear power plants became subject to safety assessments as stress test programs. The objective was to check and improve the capability of nuclear safety systems in withstanding damage from hazards caused by flooding, earthquakes, terrorist attack or aircraft collision. The two most important nuclear accidents which are considered after the Fukushima accident are loss of ultimate heat sink (LUHS) and station blackout. The LUHS is one of the most important accidents, which can be recognized as a severe accident and is caused by severe natural phenomena. In this paper, for the first time, the LUHS accident and its management as a stress test program is assessed in a VVER-1000/V446 reference nuclear reactor. By applying some portable diesel pumps which can provide long term cooling of the reactor core, steam generators and spent fuel pool with the available NPP site demineralized water for long duration; the stress test strategy is assessed. To estimate the effect of portable equipment on the NPP safety, the probabilistic safety assessment (PSA) is adopted. In this method, fault trees of engineering safety features including the proposed portable equipment and event trees of different initiating events are applied to estimate the frequency of each accident sequence. The safety of the nuclear power plant is assessed by the risk measure of core damage frequency (CDF). The calculated CDF values of LUHS accident with and without deploying the portable diesel pumps are 1.01E-11(yr−1) and 1.419E-8 (yr−1), respectively. The results indicate a significant decrease in CDF of the VVER-1000/V446 nuclear reactor for the LUHS accident by applying portable equipment, introduced as a stress test program.